Implementasi Sistem Informasi E-Learning Berbasis Odoo Studi Kasus MI YPPI 1945 Babat - Ahmad Assrorul Abidin; Nufan Balafif; Eddy Kurniawan (JELIKU (Jurnal Elektronik Ilmu Komputer Udayana), 2024)
The Odoo e-learning information system is a digital learning media to support the process of delivering material and assessing work. Adequate technological facilities at the MI YPPI 1945 Babat school are the school's main capital. Selection of website modules and e-learning modules in Odoo which are used for the display design process and filling in the database according to needs is the initial stage of implementing the Odoo e-learning system. The system can carry out the process of delivering material, assigning assignments, performance assessments, and learning target data to provide solutions to learning problems that are less interesting and less effective and efficient in schools. UAT (User Acceptance Testing) testing method with indicators of Completeness, Consistency, Tracking, Operability, Training, Security, Accuracy, Simplicity and Ease of Execution for students and teachers by taking samples of the student population using the Slovin formula and teachers using saturated samples to get sample data used to test the quality of the running system produced a percentage of 88%, which means the system runs very well at the MI YPPI 1945 Babat school.